The effect of starch- and sucrose-reduced diet accompanied by nutritional and culinary recommendations on the symptoms of irritable bowel syndrome patients with diarrhoea - Lucia Gayoso; Koldo Garcia-Etxebarria; Teresa Arzallus; Isabel Montalvo; Jacobo Lizasoain; Mauro D’Amato; Usune Etxeberria; Luis Bujanda (Therapeutic Advances in Gastroenterology, 2023)
Background: Irritable bowel syndrome (IBS) is a common gastrointestinal condition which entails a high burden in the quality of life (QoL) of patients. Nutritional interventions have been proposed to alleviate symptoms, since still no effective treatments exist for IBS. Objectives: Our aim is to analyse the feasibility of the use of starch- and sucrose-reduced diet (SSRD). Design: In this study, we used a SSRD accompanied by nutritional and culinary recommendations to measure the effects in IBS patients with diarrhoea. Methods: In all, 34 participants completed a 4-week nutritional intervention based on SSRD. Symptoms, QoL and dietary habits were assessed by several questionnaires that were completed at the beginning, daily, after 2 weeks, at the end, and after 2 months. Results: 85.29% of the participants reached the primary endpoint [reduction of 50 points or more in IBS-symptom severity scale (SSS)], and 58.82% the secondary endpoint (reduction of 50% or more in IBS-SSS). The relief of symptoms and improvement of the QoL were significant after 2 weeks of intervention, at the end and after 2 months. Dietary habits were consistent with the diet and high adherence was achieved. Conclusions: SSRD and individualized nutritional and culinary guidance improved symptoms and QoL of IBS patients with diarrhoea, with a high adherence.